“Where Now for Visible Unity?”: Commemorating Nicaea in a World with People of Other Faiths - Illert, Martin 1967- (2024)
This article provides a short introduction to the activities and the spirit of the World Council of Churches for the ecumenical year 2025 by paying particular attention to the commemoration and anniversary celebration of the First Ecumenical Council of Nicaea, which will take place in October 2025 in Egypt under the theme “Where now for visible unity?” In its main part, this article looks at the theological issues that arise 17 centuries after the Council of Nicaea proclaimed its creed and made its decisions, for both churches and Christians in their bilateral and multilateral ecumenical contacts among themselves and in relation to their engagement with believers of other faiths. Starting from these questions, the article explores what it fundamentally means to speak of visible unity of Christians and churches within a multireligious world.
Keywords: Sixth World Conference on Faith and Order; Ecumenical Year 2025; Nicaea Jubilee; Interfaith Dialogue; Visible unity of churches